The Use of Visual Learning Media to Improve Student Learning Outcomes in Social Studies Lessons in Elementary School - Ferdy Nur Adhiansyah; Hanikah Hanikah; Novan Hardiyanto (Journal of Educational Sciences, 2026)
Social studies (IPS) instruction in elementary schools is frequently delivered through lecture based methods without instructional media, contributing to low student learning outcomes. This study aimed to describe the planning, implementation, and outcomes of using visual learning media to improve third grade students’ learning outcomes on the topic of “Denah Tempat Tinggalku” (home location map) at SDN 3 Sedong Lor, Cirebon. This research employed classroom action research (CAR) based on the Kemmis and McTaggart model, carried out in two cycles, each comprising planning, action, observation, and reflection. The subjects were 23 third grade students consisting of 12 boys and 11 girls. Data were collected through observation, interviews, and learning achievement tests, then analyzed descriptively and quantitatively. The results showed that the percentage of students achieving the minimum mastery criteria (KKM) increased from 34.78% at baseline to 73.91% in Cycle I, and reached 100% in Cycle II, with the class average rising from 63.26 to 85. Teacher performance and student activity scores also increased consistently across cycles. These findings indicate that systematic use of visual learning media effectively improves students’ understanding of spatial concepts and their learning outcomes in social studies.